Cost-effectiveness of decentralising acute malnutrition treatment with a standard or simplified treatment protocol: an economic evaluation in the region of Gao, Mali - Bernardette Cichon; Noemí López-Ejeda; Salimata Samake; Cornelia Aton; Abdias Ogobara Dougnon; Mahamadou N’tji Samake; Aliou Bagayoko; Magloire Bunkembo; Alexandra Rutishauser-Perera; Pilar Charle-Cuellar (BMC Public Health)
Abstract Background Acute malnutrition treatment coverage remains low worldwide, causing significant morbidity and mortality. Decentralisation of treatment to Community Health Worker (CHW) sites has shown to be an effective strategy to improve access and increase coverage, but evidence on the cost and cost-effectiveness of this approach as well the use of simplified treatment protocols in conflict settings is lacking. The objective of this study was to determine cost per child treated as well as the cost-effectiveness of the hybrid model of treatment delivery (where treatment is provided at both health facilities and CHW sites) using either a standard protocol (Intervention 1) or simplified protocol (Intervention 2) compared to standard treatment at health facilities only (Control) in the conflict affected region of Gao in Northern Mali. Methods This economic evaluation was part of a three-arm cluster randomized controlled trial which enrolled 2038 children with moderate and severe acute malnutrition. Outcomes assessed were cost per child treated as well as average and incremental cost-effectiveness ratios for cost per child cured and disability adjusted life year (DALY) averted. A within study trial horizon, from March 2020 to July 2021, was used. Cost data were collected from accountancy records and through key informant interviews using a societal perspective. Treatment admission and outcome data were obtained from the main trial. Results In the base case scenario the cost per child treated was 272 US$, 179 US$ and 210US$ in the Control, Intervention 1 and 2 groups, respectively. Cost per child cured was 356 US$ in the Control, 219 US$ in the Intervention 1 and 226 US$ Intervention 2 groups. Ready-to-use therapeutic foods (RUTF) costs among SAM children treated with a simplified protocol were 5.7 US$ less per child. The average cost per DALY averted was 173.1 US$ in the Control compared to 60.3 US$ in the Intervention 1 and 53 US$ in the Intervention 2. Conclusion This study shows that involving CHWs in acute malnutrition treatment reduces the cost per child treated and is a cost-effective strategy, due to lower treatment costs and greater coverage in the decentralised model. Switching to a simplified protocol in a conflict setting can lead to cost savings particularly in terms of RUTF, and should be considered where weight-based admission, monitoring or dosage is not possible or RUTF stocks are running low. Trial registration The study protocol was registered under reference ISRCTN-60,973,756 on the 15th of October 2020.